The Effect of Profitability and Company Size on Firm Value With Dividend Policy as Moderation - Haryanti Fika; Fauji Sanusi; Enok Nurhayati (Institute of Advanced Knowledge and Science, 2025)
The purpose of this study is to test and prove the effect of profitability and company size on firm value by using dividend policy as a moderating variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2023. The sampling technique uses purposive sampling method with the aim of obtaining sample data in accordance with the criteria needed in the study and obtained as many as 19 companies that can be sampled with 114 data observations. The results in this study are Profitability has a significant positive effect on Company value, Company size has a negative effect on Company value, Dividend policy is able to moderate the effect of profitability on Company value by strengthening the relationship, Dividend policy is able to moderate the effect of profitability on Company value by weakening the relationship